2012
DOI: 10.1038/bmt.2012.149
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in patients with metastatic breast cancer receiving intensified chemotherapy and stem cell rescue: data from the Italian registry

Abstract: on behalf of Gruppo Italiano per il Trapianto di Midollo Osseo, Cellule staminali emopoietiche e terapia cellulare (GITMO) -Sezione Tumori SolidiThe median survival of women with metastatic breast cancer (MBC) is 18-24 months, and fewer than 5% are alive and disease free at 5 years. We report toxicity and survival in a cohort of MBC patients receiving high-dose chemotherapy (HDC) with autologous hematopoietic SCT (AHSCT) in Italy between 1990 and 2005. Data set for survival analysis has been obtained for 415 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
(41 reference statements)
2
13
0
2
Order By: Relevance
“…The present study, reporting a retrospective data analysis on HDC and AHSCT for high-risk BC in Europe, includes 1 of the largest series in this field. Because it comes from a registry and derives from patients transplanted in many cases when only limited information on tumor biology was available, many parameters are lacking, making interpretation of results more difficult [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The present study, reporting a retrospective data analysis on HDC and AHSCT for high-risk BC in Europe, includes 1 of the largest series in this field. Because it comes from a registry and derives from patients transplanted in many cases when only limited information on tumor biology was available, many parameters are lacking, making interpretation of results more difficult [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Often these patients can only be treated palliatively, and the goal is then to prolong life while trying to ensure that patients do not suffer tumor-related symptoms and are able to enjoy as good a quality of life as possible [12][13][14]. The mean life expectancy for women with breast cancer and metastatic disease is 18-33 months; the median progression-free survival is between 13.5 and 17 months [15,16]. Currently, the relative 5-year survival rate is significantly lower than 50% [15]; the relative 10-year survival rate for patients with bone metastasis is reported to be 35 % [17,18].…”
Section: Health-related Quality Of Life In Metastatic and Adjuvant Brmentioning
confidence: 99%
“…The mean life expectancy for women with breast cancer and metastatic disease is 18-33 months; the median progression-free survival is between 13.5 and 17 months [15,16]. Currently, the relative 5-year survival rate is significantly lower than 50% [15]; the relative 10-year survival rate for patients with bone metastasis is reported to be 35 % [17,18]. As medical therapies become increasingly personalized, patientsʼ health-related quality of life (HRQL) is an important indicator of the efficacy of the therapeutic intervention, particularly in patients with chronic disease.…”
Section: Health-related Quality Of Life In Metastatic and Adjuvant Brmentioning
confidence: 99%
“…The authors reported an ORR of 80% at day +100 and a CR or improved rate of approximately 45% at 1-year post-ASCT.THIO is a polyfunctional alkylating agent, similar in structure to nitrogen mustard, that damages the DNA of cancer cells and designated as an orphan drug by the European Medicines Agency on 29th January 2007. High-dose THIO appears to be with broadspectrum antitumor efficacy (43), which can be added in myeloablative multi-agent regimens for ASCT in both solid(44,45) and hematopoietic tumors(46)(47)(48)(49), and the drug was designated by the United States Food and Drug Administration as a conditioning treatment prior to ASCT on 2nd April 2007.In our study, the choice of THIO was based on the documented sensitivity of myeloma cells to the drug in the context of resistance to previous treatments (50) and the decision was made to explore a double alkylator-based regimen. The dose-limiting toxicity of THIO is notably on the gastrointestinal tract (mucositis and diarrhoea) and the central nervous system (drowsiness and seizure).…”
mentioning
confidence: 99%